Assessment of water hyacinth (Pontederia crassipes) distribution and changes in Lake Koka and Lake Ziway through remote sensing techniques - Gemechu Tolera; Abebe Getahun; Akewake Geremew; Seyoum Mengistou (Scientific Reports)
Abstract Water hyacinth is an invasive weed that significantly impacts Ethiopia’s environment and human well-being, particularly in Lake Koka and Lake Ziway. It reduces water availability and biodiversity in these areas. This study aimed to predict the spread of water hyacinth using GIS-based multi-criteria evaluation and Sentinel-2 imagery. Field collections were conducted in both lakes during the wet and dry seasons of 2020. A multivariate statistical classifier was employed to map the spatial distribution of water hyacinth. The results indicate that in Lake Koka, coverage increased from 3.87% (1455.39 ha) in the dry season to 12.44% (4678.06 ha) in the wet season. In Lake Ziway, coverage ranged from 10.01% (6526.30 ha) to 11.39% (7424.05 ha) between the seasons. These findings highlight the significant proliferation of water hyacinth during the rainy season, which harms biodiversity and socioeconomic development. Additionally, the study found a decrease in the area covered by water hyacinths in agricultural land, water bodies, and bare land. Restoring land use and monitoring weed growth regularly is essential to mitigate these effects.